Interaksi Guru Dan Orang Tua Dalam Dukungan Pendidikan Anak Usia Dini di PAUD Daru Tifli - Siti Aisah; Budi Ilham Maliki; Nuryati Nuryati; Mahsiani Mina Laili; Sanin Sudrajat (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early Childhood Education (ECE) plays a crucial role in shaping children’s character and holistic development. The success of education at this stage is influenced not only by learning processes in school but also by the quality of interaction and partnership between teachers and parents. In practice, however, teacher–parent interaction is often limited and not yet sustainable. This study aims to explore in depth the forms, meanings, and roles of teacher–parent interaction in supporting early childhood education at PAUD Daru Tifli. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with one teacher and several parents of early childhood learners, supported by direct observation. The data were analyzed using thematic analysis to identify key patterns related to teacher–parent interaction in supporting early childhood education. The findings revealed seven main themes: (1) the importance of teacher–parent interaction, (2) the role of interaction in children’s development, (3) forms of teacher and parent support, (4) communication media used, (5) communication as a means of monitoring child development, (6) responses to information about children’s development, and (7) routine discussions between teachers and parents. The results indicate that interaction is perceived as a continuous partnership that bridges the home and school environments. Emotional and communicative support was found to have a greater impact on children’s confidence and development than material support alone. The discussion highlights that consistent two-way communication, the use of digital media such as WhatsApp, and regular formal and informal discussions strengthen parental involvement and support children’s holistic development. This study recommends strengthening teacher–parent partnerships as a key strategy for improving the quality of early childhood education services